Alterations in oocyte mitochondrial number and function are related to spindle defects and occur with maternal aging in mice and humans†. Issue 4 (24th November 2018) - Pasquariello, Rolando; Ermisch, Alison F; Silva, Elena; McCormick, Sue; Logsdon, Deirdre; Barfield, Jennifer P; Schoolcraft, William B; Krisher, Rebecca L
Abstract: The objective of this work was to determine the role of mitochondria in the loss of oocyte quality with maternal aging. Our results show that mitochondrial DNA (mtDNA) copy number and function are reduced in eggs from aged mice after both in vivo and in vitro maturation. Higher incidences of spindle abnormalities were observed in old eggs. However, no correlation with egg ATP content was found. In vitro matured eggs from aged mice did not have a normal cortical distribution of active mitochondria and were subject to increased oxidative stress due to higher levels of reactive oxygen species and lower expression of glutamate-cysteine ligase, catalytic subunit ( Gclc ). Supplementation of antioxidants during in vitro maturation of old eggs mitigated this affect, resulting in increased mtDNA copy number and mitochondrial function, a mitochondria distribution pattern similar to young eggs, and improved chromosomal alignment. Eggs from women of advanced maternal age (AMA) had lower mitochondrial function than eggs from young women, although both age groups displayed a cortical distribution pattern of active mitochondria. In contrast to the mouse, human eggs from AMA women had higher mtDNA copy number than eggs from young women following in vitro maturation. In summary, oocytes of older females are more susceptible to perturbations in mitochondrial number and function, which are associated with increased spindle abnormalities and oxidative stress during in vitro maturation. These results demonstrate that oocyte mitochondria play a critical role in age-related infertility. Abstract : A decrease in mitochondrial copy number and function affects oocyte quality in aged females, and is related to increased spindle abnormalities and oxidative stress.